Harnessing hydrogen-bonding: advancements and applications in pharmaceutical co-crystallization - Devi, Preeti; Sonali Kakkar; Vikas Budhwar; Manjusha Choudhary; Jogpal, Vikas (Journal of Applied Pharmaceutical Research, 2025)
Background: In the context of supramolecular chemistry, the formation of solid-state structures that exhibit predictable form and function through the use of intermolecular interactions is known as crystal engineering. In crystal engineering, the hydrogen bonds provide a directional and strong interaction between co-formers, helping to create a stable and well-defined crystalline lattice. The formation of hydrogen bonds can modify key properties of a co-crystal, such as solubility, melting point, and mechanical properties, which are valuable in pharmaceutical applications to improve drug efficacy. Fexofenadine co-crystals have been shown to significantly enhance solubility, achieving an 11-fold increase in water and a 2.47-fold increase in hydrochloric acid solutions. Objective: The review primarily focuses on the process of recognizing molecules and forming complex assemblies that are controlled via non-covalent interactions. Methodology: Various strategies, including hydrogen bond-based co-crystal design, are discussed and elaborated upon in this review. Result and Discussion: Reliable tools for developing supramolecular architectures can be obtained by complementarily combining hydrogen bonds with the understanding of robust supramolecular synthons. In addition to bringing different molecules together, these strong supramolecular synthons play a significant role in co-crystallization by adding dimensionality and a degree of directionality to the three-dimensional solid structures. Conclusion: Accurately predicting co-crystal synthesis requires a deep understanding of supramolecular interactions and a carefully selected library of co-formers with functional groups that complement those of the target compound.